Minimally Invasive Methods in Restorative Dentistry - Biloivanenko В. В. (Actual Dentistry, 2024)
Abstract. Photopolymer composite materials have unprecedented adhesion to hard tooth tissues and correspond to the optical properties of enamel and dentin. Due to these characteristics, photopolymers are widely used in aesthetic dentistry. The purpose of this work is to evaluate the results of the step-by-step acquisition by the dentist of the manual skills of using photopolymer materials. Methods of working with dental materials on models and in the oral cavity were used. The results showed that the technique of working with modern photopolymers requires excellent manual skills, mastering them and their improvement continues constantly with the appearance of new, more advanced tools and methods of treatment in dentistry. One of the effective ways of mastering innovative work methods is the production of temporary restorations from various materials. Conclusions. During the training stages of the dentist, in cases of remote temporary filling, a mini-invasive effect can be used, since it practically does not lead to the risk of damage to the tooth and involves the manufacture of an aesthetic restoration in the future in accordance with the protocol for the treatment of permanent teeth.